DIGITAL IDENTIFICATION AND ELECTRONIC SIGNATURE: LEGAL, TECHNICAL AND SOCIAL ASPECTS (World Bulletin of Management and Law, 2025)
The article is devoted to the analysis of the institute of digital identification and electronic signature as key elements of the trust infrastructure in the context of digitalization of society. The theoretical foundations and technological approaches to establishing identity in the electronic environment are considered, legal regulation in the Russian Federation, the European Union and a number of foreign countries is analyzed. Particular attention is paid to the types of electronic signature, their legal status and cryptographic foundations of functioning. The areas of application of digital identification and electronic signature in public administration, the financial sector and business are studied. The main problems and risks associated with ensuring cybersecurity, protecting personal data and biometric information, as well as overcoming the digital divide are identified. The prospects for the development of the institute are determined taking into account the introduction of blockchain technologies, artificial intelligence and harmonization of international regulation. It is concluded that further improvement of digital identification and electronic signature requires an integrated approach, including the development of a regulatory framework, increasing the level of security and strengthening public trust